2019
DOI: 10.1016/j.adro.2018.10.003
|View full text |Cite
|
Sign up to set email alerts
|

Stereotactic MR-Guided Online Adaptive Radiation Therapy (SMART) for Ultracentral Thorax Malignancies: Results of a Phase 1 Trial

Abstract: PurposeStereotactic body radiation therapy (SBRT) is an effective treatment for oligometastatic or unresectable primary malignancies, although target proximity to organs at risk (OARs) within the ultracentral thorax (UCT) limits safe delivery of an ablative dose. Stereotactic magnetic resonance (MR)–guided online adaptive radiation therapy (SMART) may improve the therapeutic ratio using reoptimization to account for daily variation in target and OAR anatomy. This study assessed the feasibility of UCT SMART and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
147
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 155 publications
(150 citation statements)
references
References 31 publications
3
147
0
Order By: Relevance
“…A number of authors have reported on on-table adaption of treatment plans using MRgRT devices [11,[33][34][35][36][37] and also on assessing which patients benefit most from adaptive MRgRT [35,[38][39][40][41][42][43][44]. In the presented study, no online treatment plan adaptions were performed.…”
Section: Discussionmentioning
confidence: 99%
“…A number of authors have reported on on-table adaption of treatment plans using MRgRT devices [11,[33][34][35][36][37] and also on assessing which patients benefit most from adaptive MRgRT [35,[38][39][40][41][42][43][44]. In the presented study, no online treatment plan adaptions were performed.…”
Section: Discussionmentioning
confidence: 99%
“…[6][7][8] Daily, online adaptive treatment with magnetic resonance image guided RT (MRgRT) can provide an opportunity to simultaneously escalate gross tumor volume (GTV) dose while meeting OAR constraints in these difficult cases. 9 Both modeling studies 3,10,11 and completed phase I clinical trials [12][13][14] have shown the feasability of ablative dose escalation without significant adjacent organ toxicity in the central thorax and abdomen. Such trials have shown an increase in both local control and overall survival while decreasing radiation-induced toxicity events, leading to a prospective clinical trial for further evaluation in pancreatic cancer (SMART: NCT03621644).…”
Section: Introductionmentioning
confidence: 99%
“…As the use of online adaptive MRgRT has grown recently across a variety of clinics, both the potential benefits and practical difficulties of its utilization are beginning to be understood. [12][13][14][15][16][17][18][19][20][21] But ample opportunity remains for assessment and improvement of online adaptive RT as this unique treatment method continues to develop clinically. Analysis of a collection of patient data and their treatment plans in order to better understand and improve a particular RT process can proceed in a variety of ways.…”
Section: Introductionmentioning
confidence: 99%
“…Early reports have demonstrated the successful implementation of these systems into a number of clinics world-wide. Today, also a number of retrospective outcome analyses and a smaller number of phase one and phase two prospective clinical trials suggest the clinical value of investing in this technology [5][6][7].…”
Section: Introductionmentioning
confidence: 99%